Does concomitant prolactin measurement increase the accuracy of inferior petrosal sinus sampling? - YAVUZ, DİLEK; BALTACIOĞLU, FEYYAZ; HAKLAR, GONCAGÜL; APAYDIN, TUĞÇE (SPRINGER, 2022)
Introduction Prolactin (PRL) measurement during inferior petrosal sinus sampling (IPSS) can be helpful to improve the accuracy. We aimed to evaluate the effect of measuring PRL levels as a predictor for the accuracy of IPSS and evaluate its impact on the lateralization of adenomas. Methods In this retrospective cohort study, we reviewed 51 patients who had undergone IPSS for the investigation of ACTH-dependent hypercortisolism. Results Forty-nine patients had proven Cushing's disease (CD), one had EAS, and the remaining one patient had adrenal adenoma. Forty-seven patients had an above 2 ACTH IPS/P ratio at baseline, and all the post-corticotropin-releasing hormone (CRH) ACTH IPS/P ratios of patients with proven CD were above 3. In these two patients whose ACTH IPS/P ratio at baseline was below 2, PRL IPS/P ratios were above 1.8 in only the dominant side, which was considered secondary to a prolactin intersinus gradient due to the biological effects of the tumor. PRL-adjusted ACTH IPS/P ratios were > 1.3 in all patients with proven CD; it was 0.7 in the patient with EAS. Surgically confirmed positive lateralization was observed in 55.1% of patients with the ACTH gradient, but when PRL-adjusted ACTH IPS/IPS ratios were used in addition to the ACTH gradient, the ratio increased to 67.3%. Conclusion Although PRL-adjusted ACTH IPS/P ratios can be helpful to improve the accuracy of results during IPSS procedures, a prolactin intersinus gradient towards the ACTH-dominant side in patients with CD may invalidate PRL as an indicator of pituitary venous outflow.
Keywords: Cushing's disease; Bilateral inferior petrosal sinus sampling; Pituitary; Prolactin; CORTICOTROPIN-RELEASING-HORMONE; DEPENDENT CUSHINGS-SYNDROME; DIFFERENTIAL-DIAGNOSIS; DESMOPRESSIN STIMULATION; PITUITARY; DISEASE